EFFECT OF CRUDE EXTRACT AND PHYTOSTEROL FRACTION OF FUMARIA OFFICINALIS IN INDUCED HYPERTROPHIC SCAR OF RABBITS - S NOORI, HANAN; ABU‑RAGHIF, AHMED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aimed to evaluate the role of crude extract and phytosterol fraction of Fumaria officinalis in experimentally induced hypertrophic scar in rabbits. Methods: Surgical wounds were performed on day 1 with an 8‑mm biopsy punch four wounds were created on the ventral surface of the rabbit ear (in vivo) down to cartilage. Triamcinolone acetonide (TAC), crude and phytosterol extracts of F. officinalis L. are administered topically to established scars on day 31. The outcome measures included study of histopathology of skin sections, transforming growth factor beta‑1 (TGF‑β1), level, and collagen three alpha1 in skin tissue. Results: In comparison with the induced hypertrophic scar, all treatment produced a significant reduction in scores of TGFβ1, collagen III, inflammation, and measurement of SEI (p ≤ 0.01). The most significant reduction in inflammation and thickness observed in TAC and extract of crude F. officinalis L. Only crude F. officinalis L. decrease fibroblast counts in comparison to induced hypertrophic scar group and other group (p ≤ 0.05). No statistically significant differences were found between the treatment groups in terms of TGF β1and collagen III. Conclusion: Topical crude extract of F. officinalis L. was more effective in the treatment of induced hypertrophic scar as compared with phytosterol of F. officinalis L. and comparable to the effectiveness of topical TAC.